PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE TEAMS GAMES TOURNAMENT (TGT) PADA PENDIDIKAN PANCASILA SISWA KELAS III SD INPRES PACCINONGANG - Agnes Arnil K (STKIP Subang, 2024)
This research is motivated by the learning activities of students who have not achieved the presentation of success in class III SD Inpres Paccinongang. The formulation of the problem of this research is whether the application of the cooperative learning model of the Teams Games Tournament (TGT) type can improve the learning activities of Pancasila Education about the Pancasila symbol of class III students of SD Inpres Paccinongang. The purpose of this study was to determine the learning activities of Pancasila education on the Pancasila Symbol material. The approach used is a qualitative approach and the type of research is classroom action research (PTK). The subjects of this study were 25 class III students of SD Inpres Paccinongang consisting of 14 male students and 11 female students. Data were obtained through observation and documentation techniques. The data analysis technique used is a qualitative data analysis technique. The results of the study showed that in cycle I, the observation of student learning activities with sufficient qualifications (C). In cycle II, it showed an increase in observation of student learning activities with good qualifications (B). The conclusion of this study is that by implementing the cooperative learning model of the Teams Games Tournament (TGT) type, it can improve students' learning activities on the Pancasila symbol material for grade III students of SD Inpres Pacinonggang.